NALISIS KETERLIBATAN KERJA DAN DUKUNGAN ORGANISASI TERHADAP KINERJA DENGAN MEDIASI KOMITMEN ORGANISASIONAL - Adi Wisaksono (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2014)
The purpose of this study was to examine the effect of job involvement and organizational support on organizational commitment, job involvement examine the influence, organizational support and organizational commitment to performance and examine the effect of organizational commitment as a variable that mediates the effect of job involvement and organizational support. The research object is Semarang State Polytechnic lecturer. To explain the concept of variable work engagement and organizational support on organizational commitment and its impact on the performance of the lecturer then developed a research model that explains the causal relationship over these variables. The study population was tenured faculty status as civil servants (PNS) in Semarang State Polytechnic much as 352 people, with purposive sampling method sampling a total of 100 respondents were distributed, and the data of 100 questionnaires were analyzed using the data Testing analaysis regression. Mediation test done to prove that organizational commitment as a variable that mediates the effect of job involvement and support of the hypothesis being tested proven organizational. All accepted, namely that job involvement and organizational support positive significant effect on organizational commitment, job involvement, organizational support and organizational commitment have a significant effect positively to the performance of the sig (probablity significancy) is smaller than the error rate (alpha) which has been determined, that is equal to 5%. Test mediation does not prove that organizational commitment as a variable that mediates the effect of job involvement and organizational support.